The Effect of Lavender Essential Oil as A Pain Relief Post Debridement Patient - Febriza Kharisma Putri; Okti Sri Purwanti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pain is a multidimensional individual experience that can cause disruption to quality of life and chronic stress. Lavender aromatherapy combined with deep breathing is a form of non-pharmacological pain relief technique. The purpose of the study was to determine the effectiveness of lavender aromatherapy combined with deep breathing on reducing the pain scale of post-debridement patients. The method used in the study was a case study which raised a single topic with 1 subject used and had been in accordance with the predetermined criteria, and the analysis used the one group pre-test and post-test method, with pain measurement using the Numerical Rating Scale. The results of the study that had been conducted were found to show changes on the first day with a score of 8 to 7, on the 2nd day the score was 7 to 5 and on the 3rd day showed a decrease in the score from 5 to 3. The conclusion of the study that had been conducted was that lavender aromatherapy combined with deep breathing was effective in reducing pain in patients with post-scrotal debridement.